The fear factor: how one emotion connects altruists, psychopaths and everyone in-between - Marsh, Abigail (Robinson, 2020)
Whether humans are good or evil is a question that has plagued philosophers and scientists for as long as there have been philosophers and scientists. Abigail Marsh has closely studied the brains of both the worst and the best among us -- from children with psychopathic traits whose families live in fear of them, to adult altruists who have given their own kidneys to strangers. In this book, Marsh explores the human capacity for caring, drawing on research findings from clinical, translational and brain-imaging investigations on the nature of empathy, altruism and aggression, and brings us closer to understanding the basis of human social nature